Tabloidyzacja przekazu krakowskich mediów regionalnych na temat wyborów samorządowych – płaszczyzna treści - Szymańska, Agnieszka (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The paper deals with the issue of the social roles and functions of local and regional media in the modern democratic system as regards the mediatization of local politics during local government elections. It presents the results of surveys on the content of daily newspapers in Kraków conducted by Agnieszka Hess and Agnieszka Szymańska during the elections in 2006 and in 2010. This paper presents the results of an analysis of the tabloidization of the coverage of local government elections by the Kraków press in relation to its content. The results of the studies of media coverage in 2006 and in 2010 indicate a changing range of communication tasks and roles assumed by various newspapers and the intensification of the tabloidization process of media coverage as regards the manner and content of reports on the local elections.
The tabloidization of the coverage of local government elections by the regional media in Kraków – aspects of content